Feasibility study of aspect mining at requirement level - Subramaniam, Hema; Zulzalil, Hazura; A. Jabar, Marzanah; Hassan, Saadah (Indian Society for Education and Environment, 2014)
Modularity is categorized as quality characteristic which can increase the maintainability of a software program. Although modularity is gaining popularity, yet it is hard to be realized since there are many crosscutting concerns scattered and tangled in object oriented programs. Thus, more efforts are needed to maintain the software program which uses object oriented approach. On the other hand, aspect oriented approach has been viewed as it can encourage modularization. Since majority of the existing application is using object oriented approach, restructuring process known as refactoring become essential in increasing the program modularity. Refactoring means the process of restructuring the internal section without changing the system behaviour. Even though refactoring becomes the solution for this yet it does not seem to increase the modularity of a software program. This is due to lack of a comprehensive aspect mining method which helps in extracting the crosscutting concern from the existing applications before the refactoring takes place. At the present time, software practitioner preferred to conduct aspect mining at coding level which resulted in incomplete crosscutting concern extraction. Since the requirement stage being the initial stage before coding, it is believed to have the ability to extract more crosscutting concerns. Thus, it creates a space for aspect mining at requirement level as an alternative to aspect mining at coding level. In that case, the feasibility of aspect mining at requirement level becomes a need. This study aims to demonstrate the opportunity of conducting aspect mining at requirement level. Interview conducted among the Certified Professional Requirement Engineers (CPRE) has revealed that aspect mining at the requirement level is feasible and needed. The result of this study represented in SWOT analysis matrix is useful in justifying the alternative method of aspect mining. This alternative analysis also highlighted on the frequency of crosscutting concern that used among the CPRE indicating the worthiness of aspect mining at the requirement level.